Resection of cerebellar tumours causes widespread and functionally relevant white matter impairments. Issue 6 (7th January 2021) - Gomes, Carlos Alexandre; Steiner, Katharina M.; Ludolph, Nicolas; Spisak, Tamas; Ernst, Thomas M.; Mueller, Oliver; Göricke, Sophia L.; Labrenz, Franziska; Ilg, Winfried; Axmacher, Nikolai; Timmann, Dagmar
Abstract: Several diffusion tensor imaging studies reveal that white matter (WM) lesions are common in children suffering from benign cerebellar tumours who are treated with surgery only. The clinical implications of WM alterations that occur as a direct consequence of cerebellar disease have not been thoroughly studied. Here, we analysed structural and diffusion imaging data from cerebellar patients with chronic surgical lesions after resection for benign cerebellar tumours. We aimed to elucidate the impact of focal lesions of the cerebellum on WM integrity across the entire brain, and to investigate whether WM deficits were associated with behavioural impairment in three different motor tasks. Lesion symptom mapping analysis suggested that lesions in critical cerebellar regions were related to deficits in savings during an eyeblink conditioning task, as well as to deficits in motor action timing. Diffusion imaging analysis of cerebellar WM indicated that better behavioural performance was associated with higher fractional anisotropy (FA) in the superior cerebellar peduncle, cerebellum's main outflow path. Moreover, voxel‐wise analysis revealed a global pattern of WM deficits in patients within many cerebral WM tracts critical for motor and non‐motor function. Finally, we observed a positive correlation between FA and savings within cerebello‐thalamo‐cortical pathways in patients but not in controls, showing that saving effects partly depend on extracerebellar areas, and may be recruited for compensation. These results confirm that the cerebellum has extended connections with many cerebral areas involved in motor/cognitive functions, and the observed WM changes likely contribute to long‐term clinical deficits of posterior fossa tumour survivors. Abstract : We investigated the impact of focal lesions of the cerebellum on whole‐brain white matter integrity and their relationship with behavioural impairments in three different motor tasks. Better behavioural performance was linked to higher fractional anisotropy in the superior cerebellar peduncle. We also observed widespread white matter deficits in patients relative to controls within many cerebral white matter tracts critical for motor and non‐motor function.